TEORI PERILAKU KONSUMEN DALAM EKONOMI ISLAM: ANTARA KEBUTUHAN DAN KEMASLAHATAN - Azizah, Dini Nur; Dinda Aprilia; Hanifuloh El’Aliy (CV. KAMPUS AKADEMIK PUBLISING, 2025)
With an emphasis on the balance between fulfilling needs and achieving benefits (maslahah), this study examines consumer behavior theory from an Islamic economic perspective. According to traditional economics, the goal of maximizing utility, or personal satisfaction, typically drives consumer behavior. However, according to the principle of maqasid al-shariah, consumption behavior in Islamic economics is evaluated not only based on material satisfaction but also on moral, spiritual, and social qualities. According to Islam, consumption must uphold the five main objectives of sharia: wealth, religion, life, intellect, and progeny. To ensure consumption remains within the boundaries of halal (permissible), thayyib (good), and not excessive (israf), consumption values such as justice, cleanliness, simplicity, charity, and morality serve as guidelines. The three degrees of human needs dharuriyat (primary), hajiyat (secondary), and tahsiniyat (tertiary) that are aimed at attaining success in this life as well as the next are also explained in this research from an Islamic standpoint. Islamic consumer behavior theory offers an option that strikes a balance between the interests of people, society, and the environment in a contemporary setting marked by a consumerist and materialistic culture. Islamic economics promotes fair, sustainable, and community-focused consumerism through a methodology based on spiritual values, ethics, and social consciousness.